Patient Characteristics, Diagnostic Delays, Treatment Patterns, Treatment Outcomes, Comorbidities, and Treatment Costs of Acromegaly in China: A Nationwide Study - Guo, Xiaopeng; Wang, Kailu; Yu, Siyue; Gao, Lu; Wang, Zihao; Zhu, Huijuan; Xing, Bing; Zhang, Shuyang; Dong, Dong (Frontiers in Endocrinology, 2020)
Purpose: Acromegaly is a rare, intractable endocrine disease. We aimed to describe the patient characteristics, diagnostic delays, treatment patterns, treatment outcomes, comorbidities and treatment costs of acromegaly in China. Methods: This is a nationwide cross-sectional study. Patients diagnosed with and treated for acromegaly between 1996 and 2019 across China were surveyed via the Chinese Association of Patients with Acromegaly platform. Results: In total, 473 patients (58.8% females, mean age at diagnosis: 39.4±9.5 years) were included. The median disease duration was 3 years. The most common symptoms were extremity enlargement (91.8%) and facial changes (90.1%). Overall, 63.0% of patients experienced diagnostic delays within healthcare systems; 63.8% of the delays were <1 year. The most common first-line therapy was surgery with a transsphenoidal (76.1%) or transcranial approach (3.2%). Somatostatin analogues or dopamine agonists were administered in 20.5% of the patients as first-line therapies and in 41.7% as adjuvant therapies. Radiotherapy was performed in 32.1% of patients, 99.3% of whom received radiotherapy as an adjuvant therapy. After a median 5-year follow-up, 46.2% achieved biochemical control. Comorbidities were reported in 88.2% of the patients at follow-up; memory deterioration and thyroid nodules were the most common. Controlled patients had greater improvements in symptoms and comorbidities during follow-up than uncontrolled patients. The annual per-capita cost-of-treatment was 11013 in 2018, with medical treatments being the largest contributor (67%). Medical insurance covered 47.2% of all treatment costs. Conclusion: This study provides the first comprehensive description of real-world acromegaly data in China, serving as a basis for future population-based studies.